Neurotoxicity among pesticide applicators exposed to organophosphates. Issue 10 (October 1995) - Stokes, L; Stark, A; Marshall, E; Narang, A
Abstract : OBJECTIVES--An epidemiological study of 90 male pesticide applicators licensed in New York was conducted to investigate the effect of exposure to organophosphate pesticides on the peripheral nervous system. METHODS--A cohort of farmers and pesticide applicators from New York State were questioned off season (November 1988-February 1989) and again during the spraying season (April 1989-August 1989) about the presence of several acute signs and symptoms. Short term exposure was validated by measuring the concentration of dimethylthiophosphate (DMTP), a metabolite of guthion, in urine. Chronic signs of subtle peripheral nerve damage were determined by vibration threshold sensitivity of the farmers and applicators tested during November 1988-February 1989 and compared with controls drawn from the general population who were tested during the same time period the next year (November 1989-February 1990). Vibration threshold sensitivity was determined for both the hands and feet. Long term exposure to pesticides was determined by questionnaire. RESULTS--Paired t tests show that mean vibration threshold scores were significantly higher for the dominant (P < 0.00) and non-dominant (P < 0.04) hands among pesticide applicators when compared with scores for population based controls individually matched on age, sex, and county of residence. CONCLUSIONS--A significant increase in mean vibration threshold sensitivity for the dominant and non-dominant hand suggests previous organophosphate exposure among pesticide applicators was associated with a loss of peripheral nerve function.